Analisa Pengaruh Variasi Transmisi Dan Beban Penumpang Terhadap Konsumsi Energi Sepeda Motor Listrik Konversi Pada Kondisi Jalan Menanjak - Mariata, I Ketut; Widiyarta, I Made; Darma, I Wayan Arya (Teknik Desain Mekanika; Vol 14 No 1 (2025): Januari 2025 : Teknik Desain Mekanika, 2025)
Abstractt Electric conversion motorcycles are vehicles that operate using alternative fuel sources, specifically electric energy. These conversions require substantial power to operate effectively, which can be influenced by road conditions and passenger load during travel. Therefore, testing is necessary to understand the performance of electric motorcycles on uphill roads with varying transmission ratios and passenger loads, and their impact on electric motorcycle power consumption. In this study, a 2006 Yamaha Mio Sporty motorcycle was converted into an electric motorcycle. Converting the motorcycle to use batteries as the energy source involves modifying motor components. Unused components are removed, while new components are added to support the motorcycle's operation. Transmission ratios, which support the motorcycle's operation, were varied into three ratios (adding 12 rings, 2 rings, and no additional rings). These ratios were tested on a 12° uphill road with and without passenger load at Speed Control I and II. The testing was repeated three times to obtain the average energy consumption. It was found that the most effective transmission ratio with passenger load was a ratio of 0.92, with the addition of two rings at Speed Control II, consuming 0.065 kWh/km and achieving an average maximum speed of 11 km/h for the electric motorcycle. Without additional passenger load, the optimal transmission ratio was 0.8, consuming 0.036 kWh/km at Speed Control II, achieving an average maximum speed of 16 km/h for the electric motorcycle. This occurs because the less time the motorcycle needs to travel a 0,25 km uphill track, the less energy the electric motorcycle consumes. . Keywords: Electric Motorcyle Conversion, Energy Consumption, Transmission Ratio